Omadacycline: development of a novel aminomethylcycline antibiotic for treating drug-resistant bacterial infections. (November 2016) - Villano, Stephen; Steenbergen, Judith; Loh, Evan
Omadacycline is a first-in-class aminomethylcycline antibiotic that circumvents common tetracycline resistance mechanisms. In vitro omadacycline has potent activity against Gram-positive aerobic bacteria including methicillin-resistant Staphylococcus aureus, penicillin-resistant and multidrug-resistant Streptococcus pneumoniae, and vancomycin-resistant Enterococcus spp. It is also active against common Gram-negative aerobes, some anaerobes and atypical bacteria including Legionella spp. and Chlamydia spp. Ongoing Phase III clinical trials with omadacycline are investigating once daily doses of 100 mg intravenously followed by once-daily doses of 300 mg orally for the treatment of acute bacterial skin and skin structure infections and community-acquired bacterial pneumonia. This paper provides an overview of the microbiology, nonclinical evaluations, clinical pharmacology and initial clinical experience with omadacycline.